Risk Factors and Complications Following Percutaneous Endoscopic Gastrostomy: A Case Series of 1041 Patients - Hans-Jürgen Richter-Schrag; Sabine Richter; Olaf Ruthmann; Manfred Olschewski; Ulrich Theodor Hopt; Andreas Fischer (Canadian Journal of Gastroenterology)
BACKGROUND: Most studies exclude patients with severe coagulation disorders or those taking anticoagulants when evaluating the outcomes of percutaneous endoscopic gastrostomy (PEG).